2022
DOI: 10.3389/fgene.2022.793278
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposures to Common Phthalates and Prevalent Phthalate Alternatives and Infant DNA Methylation at Birth

Abstract: Phthalates are a diverse group of chemicals used in consumer products. Because they are so widespread, exposure to these compounds is nearly unavoidable. Recently, growing scientific consensus has suggested that phthalates produce health effects in developing infants and children. These effects may be mediated through mechanisms related to the epigenome, the constellation of mitotically heritable chemical marks and small compounds that guide transcription and translation. The present study examined the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…However, a study in Taiwan showed an inverse association between small gestational age (SGA) and maternal MnBP exposure in female neonates [43] . Sex-speci c effects of some phthalates on methylation and expression of genes in the placenta and cord blood have been reported in previous studies [13,44,45] . Moreover, phthalate exposure may adversely in uence fetal development parameters, such as gestational age reduction and preterm delivery, with a signi cant gender impact [46] .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, a study in Taiwan showed an inverse association between small gestational age (SGA) and maternal MnBP exposure in female neonates [43] . Sex-speci c effects of some phthalates on methylation and expression of genes in the placenta and cord blood have been reported in previous studies [13,44,45] . Moreover, phthalate exposure may adversely in uence fetal development parameters, such as gestational age reduction and preterm delivery, with a signi cant gender impact [46] .…”
Section: Discussionsupporting
confidence: 52%
“…Several of these functional categories, such as the regulation of small GTPase-mediated signal transduction and positive regulation of GTPase activity, were involved in biological processes in cord blood MEOHP. Another study demonstrated a similar function in different phthalate metabolites, such as butylbenzylphthalate (BBzP), which is related to small GTPase-mediated signal transduction only in female infants 45 . In the present study, embryonic cleavage, positive regulation of mitotic metaphase, and mitotic sister chromatid separation were highly signi cant in cord blood MnBP.…”
Section: Discussionmentioning
confidence: 95%
“…Although cohort studies in humans have shown an association between maternal phthalate exposure and DNA methylation changes in cord blood samples 13 20 , the results have been inconsistent, likely because of differences in epigenetic profiles according to race or ethnicity, sex, and age. More research is needed to gain, insight into the mechanisms of the effects of prenatal phthalate exposure is important for developing prevention strategies to mitigate phthalate-associated health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…As DNA methylation is tissue- and age-specific, results of these studies are not directly comparable. Several other studies of prenatal bisphenol and phthalate exposure, using an epigenome-wide approach, have identified differential DNA methylation at multiple CpG sites in cord blood in relation to exposure to different phthalates or bisphenols [ 20 25 ]. In addition, one study explored the associations of prenatal exposure to phthalates with DNA methylation in peripheral blood and buccal epithelial cells during childhood [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one study explored the associations of prenatal exposure to phthalates with DNA methylation in peripheral blood and buccal epithelial cells during childhood [ 26 ]. When exploring the associations with DNA methylation in cord blood, only the studies by Miura et al and Petroff et al included more than 70 mother–child pairs and the studies by Chen et al and Petroff et al were the only studies that included a phthalate [ 20 , 22 , 24 , 25 ]. Most previous studies that assessed the associations of maternal phthalate or bisphenol urine concentrations with DNA methylation focused on one or a few phthalates or bisphenols and did not consider joint effects of the exposures [ 15 30 ].…”
Section: Introductionmentioning
confidence: 99%